Darülfünun Öğrencilerinin Balkan Savaşı Eylemleri ve Edirne Seyahati - (:unkn) unknown (My University, 2004)
Sadrazam Küçük Said Paşa'nın (1840-1914), 16 Temmuz 1912'de istifası üzerine Gazi Ahmed Muhtar Paşa (1839-1919) sadrazamlığa getirilmiştir. Yeni hükümet 22 Temmuz 1912'de yaptığı ilk toplantısında, 25 Nisan 1909'dan beri süregelen sıkıyönetimin kaldırılmasını ele almış ve sıkıyönetim 24 Temmuz 19I2'den itibaren kaldırılmıştır. Sıkıyönetimin kaldırılması üzerine gösteriler için ortam oluşmuş ve Ekim ayının ilk haftası içinde üç gösteri yapılmıştır. Bunlardan İkisi doğrudan doğruya Darülfünun öğrencileri tarafından düzenlenmiştir. Diğeri ise İttihat ve Terakki Cemiyeti tarafından düzenlenmiş olup, öğrenciler de bu gösteriye katılmıştır. Bu gösteriler, Balkan devletlerinin Türkiye ile savaşa hazırlanmasına karşılık hükümetin hareketsiz kalması ve gereken önlemleri almaması üzerine düzenlenmiş ve iktidarı kaybetmiş olan İttihat ve Terakki Cemiyeti tarafından yönlendirilmiştir.

In the prelude of the first Balkan War (1912-13) Gazi Ahmed Muhtar Pasha was appointed Grand Vizier. The first action of his cabinet was to remove the martial law in July 1912. This provided suitable conditions for political actions İn Istanbul. The Government's apathy towards the war preparations undertaken by the Balkan states to end the Ottoman rule led Darülfünun (University) students to make demonstrations in order to urge the government to take actions. As a result of these demonstrations, the Government re-instituted the martial law and started to undertake reforms in Rumeli instigated by European powers. As Serbian and Bulgarian forces entered Ottoman territories on 16th October 1912, the Ottoman government declared war the day after. The city of Edirne was besieged by the Bulgarian army and the city had to survive under deplorable conditions until 22nd July 1913 when the Ottoman forces reclaimed the city in 1913. Right after the release of the Edirne, Darülfünun students initiated an aid campaign and organised a journey to the city in order to convey the aid material to its citizens who had much suffered during the occupation.
Darülfünun Students' Demonstrations for the Balkan War and their Journey to Edirne
Keywords: Tarih